The association between family support and compliance in undergoing antenatal care in pregnant women at Puskesmas Kasihan I - Aidatus Isro Umairoh; Afi Lutfiyati (Universitas Jenderal Achmad Yani Yogyakarta, 2026)
Background: Family support is one of the factors that influence antenatal care screening. Irregular visits to ANC result in a lack of supervision on mother and baby conditions, pregnancy complications, and the birthing process which endanger the mother and the baby.Objective: Learning the association between family support and compliance in ANC for pregnant women at Puskesmas (Community Health Center) Kasihan I.Methods: This research is a quantitative study with a cross-sectional design. The sampling technique used was accidental sampling. The sample was 53 respondents. The data collection was conducted using questionnaires and observation of the KIA book. The statistical test used was the Spearman test.Results: Family support for pregnant women at Puskesmas Kasihan I was mostly in the sufficient category of 29 mothers (54.7%). Most mothers' compliance in undergoing ANC was non-compliant with 30 mothers (56.6%). The Spearman test results showed a significance level of p-value 0.003 (p-value <0.05) and a correlation coefficient of 0.406.Conclusion: There is a association between family support and adherence to conducting ANC on pregnant women at Puskesmas Kasihan I with moderate relationship closeness.